Administrative enforcement of the demolition order for building structures construction arbitrariness - Strożek-Kucharska, Magdalena (The Opole Studies in Administration and Law, 2020)
Construction arbitrariness occurs when a construction object (or part of it) under construction or built was built (or is being built) without the required building permit or without the required construction notification, or despite objection to that notification. The law indicates which building objects do not require a building permit, which require a permit, and which are subject to notification only. In connection with the above, the construction of buildings without the required permit or notification (if the law requires these activities) must be treated as a construction permit, in other words as a pathological condition in which the construction process was started (and often also completed) without compliance required procedures by law. By stigmatizing such behavior, when it is not possible to legalize actions already taken, the administrative body is obliged to oblige the owner of the property in the form of an administrative decision to demolish a building constructed without the required permit or notification. On the other hand, as it will be shown in the further part of the study, enforcement of the obligation to demolish the building resulting from building arbitrariness will be carried out on the basis of the provisions of the Act on enforcement proceedings in administration. This is due to the fact that the demolition of a construction object resulting from building arbitrariness should be classified as a publiclaw obligation. Firstly, due to the fact that the content of the obligation (in accordance with the above-mentioned views of science representatives) results from the administrative act of the administrative body (in this case from the administrative decision). Secondly, the administrative decision regarding the necessity of demolition of a construction object resulting from building arbitrariness defines the entity (the addressee of the decision) which is obliged to take the actions specified in the decision. Thirdly, it indicates what the obligation imposed by way of decision (in this case, the demolition of a building object) and indicates the deadline for its implementation (whose ineffective expiry will result in taking action under the Act on enforcement proceedings in administration aimed at forcing the addressee to perform an obligation which he does not want or cannot perform voluntarily). Thus, there is no doubt that the obligation imposed by way of administrative decision to demolish a building object (or under construction) without the required permit or notification belongs to the public law obligations justifying its implementation under the Act on administrative enforcement proceedings.